The story of God. Season one [videorecording (DVD)] (20th Century Fox Home Entertainment, 2016)
The power of religion touches all of our lives, no matter what our faith is. This is Morgan Freeman's journey to discover how our beliefs connect us all. The quest of our generation. This is The Story of God.